THE ROLE OF HEALTH EDUCATION IN IMPROVING ADOLESCENTS' KNOWLEDGE PERTAINING TO HUMAN IMMUNODEFICIENCY VIRUS - Solichah, Nur Umi Aminatus; Setyawati, Anita (Journal of Maternity Care and Reproductive Health, 2025)
The prevalence of HIV among adolescents is experiencing a substantial rise.  A significant factor to this increase is adolescents' insufficient understanding of HIV, its transmission, and preventative methods.  Adolescents with a limited understanding of HIV may engage in promiscuity due to their ignorance of the repercussions of their behaviour.  This study aimed to assess adolescents' knowledge following health education on HIV.  This research employed a quantitative methodology with a pretest-posttest design, comprising 28 pupils from Kedawung 1 Public Junior High School.  A questionnaire assessing HIV awareness was administered to respondents prior to (pretest) and after (posttest) the health education intervention.  The collected data were analysed to ascertain the frequency distribution of respondents exhibiting proficient knowledge in both the pretest and posttest.  The findings of this study demonstrate that the proportion of teenage girls exhibiting proficient knowledge rose from 10.7% in the pretest to 85.7% in the posttest.  Parental, educational, healthcare, and academic support is crucial for adolescent to effectively apply the HIV prevention and treatment strategies acquired through health education.